1994
DOI: 10.1007/bf01255273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of induction and repair of DNA double-strand breaks by ionizing radiation: Some contradictions

Abstract: The various aspects of formation and repair of radiation-induced double-strand breaks (DSB) are summarized. Concerning the structure of DSB found in irradiated cells, enzymatic and microdosimetric analysis hints at complex damage of the DNA structure at the position of a DSB. With increasing LET, the DSB damage may be more complex than that induced by low-LET irradiation. Most of the DSB are repaired in the irradiated cell; apparently the kinetics of DSB repair and the fraction of unrejoined DSB determine cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 108 publications
(103 reference statements)
0
13
0
1
Order By: Relevance
“…The problem can also be approached with experimental investigations of the DNA damages and their repairability (Hagen 1994). For example, it has now been shown that DSB rejoining in cells is less after high-LET than after low-LET irradiation (Jenner et al 1993), and that the probability of a DSB leading to cell inactivation is highly dependent on the DSB-inducing agent, being greatest for high-LET radiation, much less for low-LET and much less again for hydrogen peroxide (Prise 1994).…”
Section: Severity Of Clustered Lesionsmentioning
confidence: 99%
“…The problem can also be approached with experimental investigations of the DNA damages and their repairability (Hagen 1994). For example, it has now been shown that DSB rejoining in cells is less after high-LET than after low-LET irradiation (Jenner et al 1993), and that the probability of a DSB leading to cell inactivation is highly dependent on the DSB-inducing agent, being greatest for high-LET radiation, much less for low-LET and much less again for hydrogen peroxide (Prise 1994).…”
Section: Severity Of Clustered Lesionsmentioning
confidence: 99%
“…High LET irradiation is defined as an irradiation beam consisting of ionized atoms heavier than helium. It has been proposed that high LET irradiation produces predominantly DSBs, while low LET radiation, X-rays and g-rays, mainly produces DNA single-strand breaks and oxidative damage (Hagen 1994;Goodhead 1995). High LET irradiation has been generally accepted as an effective therapy for cancer, and mutagenesis using heavy-ion beams has become a useful tool for plant and crop breeding (Jones 2006;Tanaka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many different definitions of clustered damage -together with interpretations of the mechanisms determining its biological relevance -can be found in the literature [2][3][4][5][6]. A major problem related to such interpretations is the lack of clear experimental results on what a doublestrand break (dsb) or a clustered lesion really is [7], thus making the definition of a one-to-one relationship between what is modelled and what is measured problematic.…”
Section: Introductionmentioning
confidence: 99%